Pengolahan Jahe Merah (Zingiber Officinale Var Rubrum Rhizoma) Menjadi Serbuk Jahe Merah (SJM) Sebagai Produk Potensial Desa Kelindang Atas - Aliyanti Aliyanti Zumrona; Lia Lia; Nadiya Nadiya; Selvia Selvia; Yossie Yumiyati (Jurnal Dehasen Untuk Negeri, 2023)
Red ginger (Zingiber Officinale Var Rubrum Rhizoma ) is a spice plant that has high potential to be developed as a value-added product. In the village of Kelindang Atas, red ginger plants are a source of income for the local community, but this potential has not been maximized due to a lack of knowledge and skills in red ginger processing. In Student Community Service (PMM) by the Faculty of Agriculture team, socialization was given to villagers regarding processing, packaging, and calculation of HPP from red ginger powder (SJM) as a red ginger processed product to increase the selling value of red ginger as a potential product from Kelindang Atas Village. Community service in the processing of red ginger in Kelindang Atas Village provides benefits in increasing the knowledge, skills and income of the local community through the sale of red ginger powder products produced